Students’ use of paper and pen versus digital media in university environments for writing and reading – a cross-cultural exploration - Vincent, Jane (Journal of Print and Media Technology Research, 2023)
This paper offers a summative cross cultural analysis of qualitative survey data collected to investigate the impact of digital media on writing and reading within universities from different countries. It addresses the particular aspect of the student’s experiences of paper and pen versus digital media. This study is based on the results of individual qualitative research conducted in 10 countries in two continents by members of the COST Action FP1104, Work Group 1 – Customers and Users. The methodological approach used is qualitative content analysis of the reported research and analysis of the indi- vidual country surveys. The survey was conducted in the national language of each country using the same research questions. Various survey methods were deployed – online questionnaire; questionnaire and interviews or hand written essays. The principal results show that there are many similarities between the countries studied but that some use pen and paper less whereas others are more prepared to use hand writing, this may link to the availability and use of digital technologies as well as to personal preferences. Reading and writing competencies are changing with the use of digital technologies but students still see benefits of reading and writing with paper which they continue to use, especially to convey private emotions and intimate feelings. This study provides new learning about the contrasting use of paper and digital media within an educational rather than business setting. These surveys provided the basis for the design and analysis of a follow up quantitative study (not examined in this paper) and for further exploration of this important research topic within the countries surveyed, particularly in social sciences and pedagogical studies.